Analisis E-WOM (Electronic Word of Mouth) dan promosi digital dalam meningkatkan keputusan pembelian pada NaufalGallery - Kencana P, Muhammad Heri; Handayani, Eva Mayfa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
Advances in information technology have driven major transformations in consumer behavior, including in the MSME sector. One important aspect is Electronic Word of Mouth (E-WOM) and digital promotion, which have been proven to influence purchasing decisions. This study aims to analyze the role of E-WOM and digital promotion in increasing consumer purchasing decisions at NaufalGallery MSMEs. The research method used is descriptive qualitative, employing in-depth interviews with the owner, employees, and 16 consumers of NaufalGallery. The results indicate that positive reviews, recommendations, personal experiences, and the credibility of information within E-WOM significantly influence consumers' interest and confidence in making purchases. Meanwhile, the quality of promotional content, promotion frequency, media used, interactivity, and visual appeal of digital promotions were found to enhance consumer engagement and strengthen purchasing decisions. This study contributes theoretically to enriching the literature on SME-based digital marketing and provides practical implications for small business owners to enhance the effectiveness of their digital communication strategies.